1990
DOI: 10.1128/jcm.28.6.1089-1093.1990
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Borrelia burgdorferi using the polymerase chain reaction

Abstract: Segments of the ospA gene of Borrelia burgdorferi were amplified by the polymerase chain reaction (PCR). Oligonucleotide primers used in the reaction flank a 309-base-pair segment within the ospA gene. After 35 cycles of amplification, the product could be detected by agarose gel electrophoresis or dot hybridization with a 32P-labeled probe. This segment was amplified in all strains of B. burgdorferi tested, but it was not detected in other bacterial species. An additional primer pair which has a broad specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 28 publications
(28 reference statements)
1
34
0
Order By: Relevance
“…Recently, several PCR assays for the detection of B. burgdorfedi based on flagellin, ospA, rRNA, or randomly cloned chromosomal gene sequences have been described (33,39,42,45,46,60,62). Thus far, there have been only a few reports that have described the use of PCR on clinical samples from patients with skin manifestations in the early and chronic 4 4 .4V…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several PCR assays for the detection of B. burgdorfedi based on flagellin, ospA, rRNA, or randomly cloned chromosomal gene sequences have been described (33,39,42,45,46,60,62). Thus far, there have been only a few reports that have described the use of PCR on clinical samples from patients with skin manifestations in the early and chronic 4 4 .4V…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, culturing is not used as a routine method. Recently, PCR, which has been shown to provide both high sensitivity and specificity (47), has been applied for the detection of B. burgdorferi DNA (33,39,42,45,46,60,62) in the tissues of infected ticks (41) and in several species of mammals (1,5,20,31), as well as in human specimens, such as cerebrospinal and synovial fluid, (11,21,23,24,26,27,29,30,32,40), urine (16,21,23,30,34), blood (15,17,34), and skin (35,43,44,49,52). However, the specificity and sensitivity of PCR with respect to individual primer pairs corresponding to the polymorphic ospA gene (58) have not been evaluated.…”
mentioning
confidence: 99%
“…From a diagnostic viewpoint, the optimal target DNA sequence should be B. burgdorfen specific, but it should also be conserved in all B. burgdorferi strains. The OspA gene, which encodes a species-specific outer surface protein (6), has been used as a template in PCR (11,34,39,43). However, not all strains could be amplified (11,39,43).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the paucity of spirochetes in pathological lesions and clinical specimens, diagnostic amplification of specific DNA sequences by the polymerase chain reaction (PCR) (47) seemed an obvious solution to this problem. Several sensitive PCR assays for detection of either purified B. burgdorferi DNA or in vitrocultivated spirochetes have been reported (34,39,46,51). We recently compared the diagnostic sensitivity of in vitro culture and PCR for the detection of B. burgdorfen in tissues from experimentally infected animals and found that PCR is superior in terms of ease and sensitivity (33).…”
mentioning
confidence: 99%
“…. Chou, 1990Mahalingam et al, 1990Saito et al, 1989Telenti et al, 1990aArthur et al, 1989Telenti et al, 1990bGodec et al, 1990Ho-Terry et al, 1990Rotbart et al, 1990Pang et al, 1990Lyman et al, 1990Kwok et al, 1988d'Auriol et al, 1990Lee et al, 1989Kristiansen et al, 1991van Ketel et al, 1990Kaneko et al, 1990Sjobring et al, 1990Plikaytis et al, 1990Williams et al, 1990Hay et al, 1990Malloy et al, 1990Goodman et al, 1991Holliman et al, 1990Brezin et al, 1990Brezin et al, M o m et al, 1989 'including from paraffin sections…”
Section: Inhibitorsmentioning
confidence: 99%